Calcium‐phosphate and parathyroid intradialytic profiles: A potential aid for tailoring the dialysate calcium content of patients on different hemodialysis schedules. Issue 4 (26th March 2015) - Ferraresi, Martina; Pia, Anna; Guzzo, Gabriella; Vigotti, Federica Neve; Mongilardi, Elena; Nazha, Marta; Aroasio, Emiliano; Gonella, Cinzia; Avagnina, Paolo; Piccoli, Giorgina Barbara
Abstract Severe hyperparathyroidism is a challenge on hemodialysis. The definition of dialysate calcium (Ca) is a pending issue with renewed importance in cases of individualized dialysis schedules and of portable home dialysis machines with low‐flow dialysate. Direct measurement of calcium mass transfer is complex and is imprecisely reflected by differences in start‐to‐end of dialysis Ca levels. The study was performed in a dialysis unit dedicated to home hemodialysis and to critical patients with wide use of daily and tailored schedules. The Ca‐phosphate (P)‐parathyroid hormone (PTH) profile includes creatinine, urea, total and ionized Ca, albumin, sodium, potassium, P, PTH levels at start, mid, and end of dialysis. "Severe" secondary hyperparathyroidism was defined as PTH > 300 pg/mL for ≥3 months. Four schedules were tested: conventional dialysis (polysulfone dialyzer 1.8–2.1 m2), with dialysate Ca 1.5 or 1.75 mmol/L, NxStage (Ca 1.5 mmol/L), and NxStage plus intradialytic Ca infusion. Dosages of vitamin D, calcium, phosphate binders, and Ca mimetic agents were adjusted monthly. Eighty Ca‐P‐PTH profiles were collected in 12 patients. Serum phosphate was efficiently reduced by all techniques. No differences in start‐to‐end PTH and Ca levels on dialysis were observed in patients with PTH levels < 300 pg/mL. Conversely, Ca levels in "severe" secondary hyperparathyroid patients significantly increased and PTH decreased during dialysis on all schedules except on Nxstage (P < 0.05). Our data support the need for tailored dialysate Ca content, even on "low‐flow" daily home dialysis, in "severe" secondary hyperparathyroid patients in order to increase the therapeutic potentials of the new dialysis techniques.